UPAYA MENUMBUHKAN MOTIVASI KERJA GURU DAN TENAGA KEPENDIDIKAN DALAM OPTIMALISASI MANAJEMEN KETENAGAAN - Ismail, Agung Deddiliawan; Jamil, Anis Farida (Universitas Djuanda, 2019)
Teacher competency improvement can be realized through increased work motivation.Motivation of teacher work is an encouragement that is possessed by a teacher to always workhard and face all problems in the hope of achieving the best results. Muhammadiyah 2 BatuMiddle School has problems in increasing the work motivation of teachers and education staff.The service activities carried out aim as an effort to foster the motivation of work of teachers andeducation staff in optimizing staff management. The method implemented in this activity is theprocurement of seminars. There are three techniques used in the delivery of material, namely 1)lecture, 2) question and answer, and 3) giving a questionnaire. The results of the materialdelivery activities aim to change the views of teachers and education personnel regarding theirduties and obligations in accordance with the government regulation number 19 of 2017. In thequestion and answer activities active participants ask regarding the consistency of workmotivation and the implementation of good learning. The questionnaire which aims to evaluateitself, produces 94% of teachers and education staff have work motivation and motivation toadvance the school.